Menilik Pembatasan Kebebasan Beragama dan Berkeyakinan dalam Perkawinan Beda Agama di Indonesia - Fransiska Widyawati (Institut Filsafat dan Teknologi Kreatif Ledalero, 2023)
Abstract: The right to marry and the right to practice a religion are fundamental human rights that are not mutually exclusive. The fulfilment of one does not necessitate the compromise of the other. However, in Indonesia, many couples from diverse religious backgrounds face complexities in exercising these rights due to the constraintsimposed by Marriage Law Number 1 of 1974, which does not explicitly accommodate interfaith marriages. According to this law, the legal recognition of a marriage necessitates a religious ceremony, and religious institutions often resist interfaith marriages. They typically urge couples from different religions to adopt a common faith to facilitate their acceptance into matrimony. This requirement often compels individuals to convert to their partner’s religion, thereby challenging their freedom of religion and belief. In the pursuit of a legally recognized marriage, individuals may find themselves coerced into relinquishing their religious freedom. This article examines the challenges faced in actualizing human rights and religious freedom in Indonesia within the context of interfaithmarriages. The methodology employed is Critical Discourses Analysis (CDA), a critical study based on text (in this case, Marriage Law No. 1/194) and context (random examples). Through critical analysis, this article posits that government regulations requiring legal recognition of marriages by religious institutions serve as an impediment to the fulfilment of religious rights and beliefs for citizens engaged in interfaith relationships. Consequently, this article advocates for amendments to the marriage regulations to actualize the human rights of freedom of religionand belief.Key words: Marriage, Human Rights, Indonesia, Marriage Law, Inter-religious Marriage